India-Korea CEPA: Harnes sing the potential in services - Nisha Taneja; Neetika Kaushal Nagpal; Saon Ray (Indian Council for Research on International Economic Relations (ICRIER), 2014)
Under India-Korea Comprehensive Economic Partnership Agreement, both India and Korea have offered trade liberalisation commitments in services. This paper examines the CEPA with the objective of identifying potential areas for harnessing services trade between the two countries. Using the Revealed Comparative Advantage (RCA) index, the paper shortlists four sectors of interest and identifies possibilities of bilateral trade flows in these sectors in the purview of existing domestic regulatory regime. Through a qualitative examination, it highlights the market access barriers and suggests areas of co-operation for enhanced trade in services. The paper also draws a comparison between the schedules of commitments offered by India and Korea under WTO revised offer and CEPA to analyse the extent of liberalisation undertaken in the bilateral agreement. The paper concludes that there are strong complementarities for services trade in sectors such as IT, transportation, construction and audiovisual services. By collaborating in these areas, India and Korea can not only strengthen their trade ties but can also gain a competitive advantage in the global market.
Keywords: L80; F13; F14; 330; Services; Trade; India; Korea; CEPA